When Policies Miss Childhood: Rethinking Indonesia’s Deradicalization Framework - Munajat Munajat; Sukron Ma’mun (Al-Jami'ah Research Centre, 2025)
This article examines the gap between regulations and practices concerning children’s deradicalization in Indonesia. The study analyses four regulations on deradicalization in comparison to the practices observed in four pesantrens (Islamic boarding schools) in the country between 2019 and 2023. The findings reveal that Indonesian deradicalization regulations remain predominantly adult-oriented and have not systematically addressed the fundamental needs of children. They emphasise nationalism, religious moderation, entrepreneurship, and rehabilitation, while education is framed merely as a mean of instilling nationalist and moderate religious values, concepts more aligned with adult-focused programmes. In contrast, the practical implementation of children’s deradicalization highlights education as their primary necessity. Education is viewed as a long-term strategy for social reintegration to ensure a better future for these children. Furthermore, critical aspects such as administrative citizenship, psychological rehabilitation, and disengagement should also receive attention. Future regulations and practices must integrate these dimensions to more effectively support the deradicalization of children associated with terrorism.[Artikel ini mengkaji disparitas antara regulasi dan praktik deradikalisasi anak di Indonesia. Studi ini menganalisis empat peraturan mengenai deradikalisasi dibandingkan dengan praktik di empat pesantren di Indonesia antara tahun 2019 dan 2023. Temuan ini menunjukkan bahwa peraturan deradikalisasi di Indonesia masih sebagian besar berorientasi pada orang dewasa dan belum secara sistematis memenuhi kebutuhan mendasar anak-anak. Peraturan-peraturan ini menekankan nasionalisme, moderasi beragama, kewirausahaan, dan rehabilitasi, sedangkan pendidikan dibingkai hanya sebagai sarana untuk menanamkan nilai-nilai nasionalis dan agama moderat, konsep ini lebih selaras dengan program yang berfokus pada deradikalisasi untuk orang dewasa. Sebaliknya, implementasi praktis deradikalisasi anak-anak menyoroti pendidikan sebagai kebutuhan utama mereka. Pendidikan dipandang sebagai strategi jangka panjang untuk reintegrasi sosial, yang menjamin masa depan yang lebih baik bagi anak-anak. Selain itu, aspek penting seperti administrasi kewarganegaraan, rehabilitasi psikologis, dan pemisihan dari kelompok mereka sebelumnya juga harus dipertimbangkan. Peraturan dan praktik di masa depan harus mengatasi dimensi-dimensi ini agar lebih efektif mendukung deradikalisasi anak-anak yang terkait dengan terorisme.]